Students’ Literacy Skills and Quality of Textbooks in Indonesian Elementary Schools - E. Oos M. Anwas; Anggi Afriansyah; Khofifa Najma Iftitah; Winci Firdaus; Yuni Sugiarti; Evi Supandi; Deni Hadiana (International Journal of Language Education, 2022)
Purpose of the study:  to find out: 1) basic literacy skills (ability to read, write and count) elementary school early grades students; (2) quality of textbooks in aspects of content, presentation, language, and graphic design; and (3) The significance of the relationship between the quality of textbooks and students' basic literacy skills.Methodology: This research uses a quantitative approach with a survey method. It was conducted in eight provinces in Indonesia. The sampling technique used stratified random sampling, 805 teachers. Data collection used a questionnaire for elementary school teachers who teach in low grades. The data analysis used descriptive statistics and correlation analysis.Main Findings: It was found that there are still relatively many early grades elementary school students who are not fluent in reading, writing, and arithmetic. These students' basic literacy skills have a significant and positive relationship with the quality of textbooks in the aspects of substance, presentation, language, and graphic design.Applications of this study: To improve basic literacy skills (reading, writing, and arithmetic) in early grades elementary school students, it is also necessary to improve the quality of textbooks in the aspects of substance/Content, presentation, language, and graphic design.Novelty/Originality of this study: It was found that there is a significant and positive relationship between basic literacy skills (reading, writing, and arithmetic) of early grades elementary school students and the quality of the textbooks they used both in terms of substance/Content, presentation, language, and graphic design.